Knowledge brief on collaborative on-farm crop testing across Africa to support climate-resilient and farmer-preferred variety development - 1000FARMS Platform (2025)
This one-page knowledge brief presents an overview of the 1000FARMS Platform, a digital and collaborative initiative to improve on-farm crop variety testing across Africa. Designed for non-specialist audiences, it highlights the platform’s purpose, key activities, tools used (such as ClimMob and the tricot approach), and early achievements. The brief targets partners, funders, and decision-makers interested in data-driven, farmer-centered innovations that accelerate climate-resilient crop breeding.